Dancing to Pay Homage to Phra That Ya Khu in Makhapuranami Puja Ceremony in Muang Fa Daet Song Yang - Yodsombat, Santi (Chophayom Journal, 2024)
Yakhu relics dance at Makhapuranami Puja in Muang Fa Daet Song Yang is a phenomenon that expresses beliefs from the ancient beliefs of the Isan people that have been passed through the present. It started as a local community and spread to urban society through worship dances. The sacred place where local faith and love are driven the social movement. The community created the sacrificial dance from their important beliefs to dance in Makhapuranami Puja tradition. The dance of Muang Fa Daet Song Yang was combined with Thai dance gestures. There are 3 groups of dances 1) dances that express greatness, 2) dances that express respect and worship, and 3) dances that express the situation, places of worship that perform for a specific purpose to worship in sacred place and people at all ages can participate this performance. The performers dress in the traditional Isan style and wear Praewa cloth as the main costume. In addition, the lyrics are melodies that convey the history from the past to the present of Kalasin province. Keyword: Dance, Belief, Sacred Place, Artificial Dance